A Multicenter, Prospective, Randomized, Double-blind Study to Evaluate the Safety and Efficacy of Saroglitazar 2 and 4 mg Compared to Pioglitazone 45 mg in Diabetic Dyslipidemia (PRESS V). (January 2014) - Pai, Vikas; Paneerselvam, A; Mukhopadhyay, Satinath; Bhansali, Anil; Kamath, Dinesh; Shankar, V; Gambhire, Dhiraj; Jani, Rajendrakumar H.; Joshi, Shashank; Patel, Pankaj
Dual PPARα/γ can improve both metabolic effects and minimized the side effects caused by either PPARα or PPARγ agonist. The PRESS V study was aimed to evaluate the safety, tolerability, and efficacy of saroglitazar 2 mg and 4 mg capsules (Lipaglyn™; Zydus Code: ZYH1) as compared to high dose pioglitazone in patients with diabetic dyslipidemia. In this 26-week double-blind, parallel arm, phase 3 study patients with hypertriglyceridemia with type 2 diabetes mellitus (BMI > 23 kg/m 2 ; hypertriglyceridemia: TG > 200 to 400 mg/dL; glycosylated hemoglobin [HbA1c ] >7 to 9%) were enrolled from 14 sites in India. After 2 weeks of lifestyle modification, 122 patients were randomized double-blind to 24-week treatment with the study drugs (saroglitazar 2 mg or 4 mg or pioglitazone 45 mg once daily) in a 1:1:1 ratio. The primary end point was change in plasma triglyceride level at week 24. The secondary end points were change in lipid profile and fasting plasma glucose at week 24. Patients who received study medication and had undergone at least 1 postbaseline efficacy evaluation were included in the efficacy analysis. All randomized patients who received at least a single dose were included for safety evaluation. The efficacy analysis included 109 patients (n = 37 in saroglitazar 2 mg; n = 39 in saroglitazar 4 mg; n = 33 in pioglitazone). Saroglitazar 2 mg and 4 mg significantly reduced ( P < .001) plasma triglyceride from baseline by 26.4% (absolute change ± SD: −78.2 ± 81.98 mg/dL) and 45% (absolute change ± SD −115.4 ± 68.11 mg/dL), respectively, as compared to pioglitazone -15.5% (absolute change ± SD: −33.3 ± 162.41 mg/dL) at week 24. Saroglitazar 4 mg treatment also demonstrated marked decrease in low-density lipoprotein (5%), very-low-density lipoprotein (45.5%), total cholesterol (7.7%), and apolipoprotein-B (10.9%). Saroglitazar treatment was generally safe and well tolerated. No serious adverse events were reported in saroglitazar treatment arm and no persistent change in laboratory parameters. Saroglitazar appeared to be an effective and safe therapeutic option for improving hypertriglyceridemia in patients with type 2 diabetes mellitus.